Peranan Manajemen Pendidikan Terhadap Kepemimpinan Kepala Sekolah - Siti Hadidah (JME Jurnal Management Education, 2023)
The school principal is the highest level of an organization in the school and certainly has a significant influence in determining the direction and policies for improving basic skills. A school leader, of course, must have education management because this is very important and a driving force for completing the process to achieve a goal. The influence and role of education management on leadership performance in schools is so great that management must be owned by every leader in every school. The method used in this study is a qualitative approach with descriptive methods. From the professional perspective of a school leader, education management is expected to influence and play a role according to its function. Therefore the researcher used a descriptive method with the tools used namely observation and interviews. The conclusion of this study refers to the National Education Standards (SNP).